Prioritization of Factors Affecting Workplace Spirituality in Tehran University of Medical Sciences - Mahdi Hajian Nosrat; Malikeh Beheshtifar (Tehran University of Medical Sciences, 2018)
Background and Aim: Workplace spirituality is an active process that strengthens people and motivates them to do purposeful activities. According to studies, several factors can promote workplace spirituality. Factors which are studied in this research include job motivation, psychological ownership, mental maturity, and moral behavior. The aim of this research is to prioritize the factors affecting workplace spirituality in Tehran University of Medical Sciences (TUMS) in 2017. Materials and Methods: This is a correlational descriptive study. The sample included 1230 staff members, of whom 294 were selected using Morgan table. To collect data, 5 questionnaires were used. And for data analysis, structural equation modeling and Amos and SPSS software were applied. Results: The findings showed that psychological ownership (path coefficient 0.110), mental maturity (path coefficient 0.172), and moral behavior (path coefficient 0.871) had an effect on workplace spirituality, but job motivation (path coefficient - 0.090) had no effect on it. Also, moral behavior, mental maturity, and psychological ownership had the greatest effect on workplace spirituality, respectively; but job motivation had no effect on it.   Conclusion: According to the results of this study, putting moral behavior as the basis, promoting mental maturity, and emphasizing psychological ownership in order of prioritizing effective factors caused workplace spirituality to increase among employees.